Molecular identification of fungi causing tissue mycoses from Formalin Fixed Paraffin Embedded (FFPE) archive specimens - Mohd Rahim, Syarifah; Ibrahim, Rosni; Tengku Jamaluddin, Tengku Zetty Maztura; Amran, Fairuz; Omar, Norhayati; Masri, Siti Norbaya (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Isolation of fungi from tissue specimens using conventional methods is time consuming. However, in some cases, the histopathological examination (HPE) of tissue alone is unable to provide a definite identity of the fun- gus. Alternatively, a non-culture method, such as polymerase chain reaction (PCR) detecting the internal transcribed spacer (ITS) rRNA genes of the fungi, is a promising diagnostic tool for rapid and accurate diagnosis of tissue myco- ses. Methods: This work investigated the utility of panfungal PCR in identifying agents of tissue mycoses in 87 FFPE archive specimens. Deoxyribonucleic acid (DNA) extraction was performed on FFPE specimens by using QIAamp DNA FFPE Tissue Kit. The ITS2 region was amplified using ITS3/ITS4 primers. The PCR products were sequenced us- ing the same primers and compared to the NCBI nucleotide database for species identification. Results: Fungal DNA was successfully amplified in 52 (59.8%) specimens, from which only 23 (44.0%) fungi were consistent with clinical/ HPE findings. The identified fungi were Aspergillus spp., Candida spp., Penicillium spp., Cryptococcus neoformans, Talaromyces marneffei, and Rhizopus oryzae. A few rare fungi were also identified, such as Diaporthe longicolla and fungus-like oomycete such as Pythium insidiosum that are commonly associated with plant pathogens. Conclusion: Although PCR was able to offer accurate genus/species identification, utilising this method on paraffinised tissue specimens must be evaluated by considering many factors that will reduce its sensitivity and specificity. Therefore, it is important to correlate the PCR results with clinical and HPE findings to obtain a correct diagnosis and adequate treatment for tissue mycoses.